Unleashing the Export Potential of Light Engineering Products: Evidence from a Firm-Level Survey (Social Science Review, 2025)
Based on a firm-level survey, this article analyzes the export potential, capacity, and challenges of the light engineering industries (LEI) in Bangladesh. The light engineering sector accounts for 2.5% of the country’s GDP and employs over 10 million people. Many of the firms operating in this industry are small-scale and decentralized, which makes them more accessible to local communities and helps in the promotion of inclusive growth. The industry's products are affordable and customized to meet the needs of local consumers, making them an essential component of the country's development strategy. However, there is a lack of credible information regarding the location of the light engineering enterprises and their export potential. The contribution of this paper is to fill this critical gap. The paper finds that the LE firms' location and specialization depend on the availability of raw materials and local demand; the firms operate with a small number of workers (less than 10) and mostly use domestic raw materials and conventional machines. However, they rarely replace their machinery, which affects productivity. Major findings also include that light engineering firms mostly produce agricultural machinery, spare parts, and machinery and parts for the construction sector, transport, textile, food processing, and molding industries. Meanwhile, the paper finds that less than 2% of the firms are currently exporting due to limited production capacity, lack of quality raw materials, insufficient capital, unskilled workers, and lack of policy support. Around 16% of the surveyed firms believe they have high export potential, whereas 82.4% of firms have no plans regarding exporting their products to the global market. To promote the industry's export competitiveness and overcome ongoing challenges, a set of policy recommendations are given, including effective policy implementation, utilization of firm-level dataset, product quality improvement, skills development, use of modern technologies, and adequate policy support from the government.Social Science Review, Vol. 41(1), June 2024, Page 121-144.